ANALISIS KORELASI DAN REGRESI DINAMIKA POPULASI HAMA DAN MUSUH ALAMI PADA BEBERAPA VARIETAS UNGGUL PADI SETELAH PENERAPAN PHT DI KABUPATEN BONE PROVINSI SULAWESI SELATAN - Ilyas, Asriyanti (Informatika Pertanian, 2013)
Different types of rice pests, have been reported. The explosions and a potential pests are Rice Stem Borer (Tryporizasp.), Brown Planthoppers (Nilaparvata lugens), Green Leafhoppers (Nephotettix virescens), and Rats (Rattus sp.), wichan obstacle in creating stability of rice production in Bone. In rice ecosystem, natural enemies of arthropod predatorsare most instrumental in suppressing the pest population. Fluctuation in population density of natural enemies, affectingpests presence. Efforts to suppress pest proportions through IPM, is a strategy of lowering the level of pests and damageto rice crops. This study aims to identify and measure the relationship strength between pests and natural enemiespopulations in some rice varieties after IPM, using correlation and regression analysis. Observations conducted in Bone,from May to August 2012, with 2 observed variables, pests and natural enemies populations in Inpari 6, Inpari 10, Inpari16, Ciherang, Cigelis, and Mekongga. Data analysis were performed using correlation and regression analysis. Theresults showed a high degree of correlation between pest and natural enemies (predators) populalions, characterized bya positive correlation coefficient (0.957) and significant at the level of 0.01, where each increase in the intensity of pestpopulations, will be followed by increase in the number of natural enemies captured.